"One for two" strategy to prepare MOF-derived NiCo2S4 nanorods grown on carbon cloth for high-performance asymmetric supercapacitors and efficient oxygen evolution reaction. (20th February 2020) - Wang, Di; Tian, Liyong; Huang, Jieyu; Li, Dawei; Liu, Jingyan; Xu, Yang; Ke, Huizhen; Wei, Qufu
Abstract: Metal-organic frameworks (MOFs) have recently emerged as promising hierarchical structured porous materials for high-performance energy storage and conversion devices due to their unique tunable structure and excellent porosity. Herein, we reported a "one for two" strategy to prepare NiCo2 S4 nanorods directly grown on carbon cloth (NiCo2 S4 @CC) via a simply modified MOFs-derived approach for high-performance asymmetric supercapacitors and efficient oxygen evolution reaction (OER). As an electrode for asymmetric supercapacitors, the NiCo2 S4 @CC electrode showed excellent electrochemical performance with high specific capacitance and good rate capability. The asymmetric supercapacitor using NiCo2 S4 @CC as a cathode electrode and N-doped porous carbon nanosheets grown on the CC (NC@CC) as an anode electrode achieved a superior energy density and power density and a long cycle life. Furthermore, the NiCo2 S4 @CC exhibited a notable electrocatalytic activity as an electrocatalyst for OER. The remarkable electrochemical performance of as-prepared NiCo2 S4 @CC could be mainly attributed to its hierarchical structure, sufficient active sites and low metal-anion bond energy after sulfuration reaction. This work could provide an unprecedented opportunity to fabricate functional materials under rational design for various applications.